High-throughput sequencing reveals omnivorous and preferential diets of the rotifer Polyarthra in situ - Liang, Diwen; Luo, Hailin; Huang, Chunrong; Ye, Zhen; Sun, Shuangshuang; Dong, Jiahua; Liang, Mingyi; Lin, Senjie; Yang, Yufeng (Frontiers in Microbiology, 2022)
Knowledge of in situ diet of widespread rotifers is crucial for accurately understanding the trophic position, ecological function, and adaptability to environmental changes in aquatic ecosystems. However, it is challenging to achieve the in situ diet information due to the lack of efficient and comprehensive methods. Here, we investigated the diet composition of Polyarthra in a subtropical lake using high-throughput sequencing (HTS) of a rRNA metabarcode for Polyarthra and ambient water samples. After eliminating Polyarthra sequences, a total of 159 operational taxonomic units (OTUs) from taxa in 15 phyla were detected from Polyarthra gut content samples. Most of the OTUs belong to Chlorophyta, followed by unclassified Fungi, Chrysophyta, Dinoflagellata, Ciliophora, Bacillariophyta, Cryptophyta, Arthropoda, Cercozoa, Mollusca, Apicomplexa, Haptophyta, Amoebozoa, Chordata and other eukaryotes. Our results showed that Polyarthra mainly grazed on Chlorophyta, which may result from the high relative abundance of Chlorophyta in ambient waters. In contrast, Chrysophyceae and Synurophyceae were enriched in Polyarthra’s gut, indicating that this rotifer prefers these taxa as food. Moreover, correlation analysis showed that total nitrogen, transparency, depth, Chlorophyll-a and total phosphorus were key factors for the variation of the eukaryotic community in the Polyarthra gut contents. When the concentration of nutrients in the water environment decreased, Polyarthra shifted from herbivorous feeding to more carnivorous feeding. Thus, Polyarthra is generally omnivorous but preference for Chrysophytes and Synurophytes, and it responds to the environmental changes by adopting a flexible feeding strategy. This could partly explain why the widespread rotifers have apparently wide tolerance toward spatial and environmental changes.